(untitled) - Muschla, Gary Robert (San Francisco, CA., 2006)
The second edition of the Writing Workshop Survival Kit offers English teachers and writing teachers in grades 5-12 a thoroughly updated and revised guide to teaching the writing process. This comprehensive, step-by-step resource is an invaluable aid for teachers who are conducting a writing workshop or managing a writing workshop in the classroom. Gary Robert Muschla explains the stages of the writing process and shows how to engage students in the dynamics of writing. The book includes activities, numerous reproducibles, and 100 mini-lessons that concentrate on various types of writing, writing techniques, and the mechanics of writing. In addition, the second edition contains new material on timely topics such as Enlisting Support for Your Writing Workshop, Using Search Engines to Find Information on the Internet, The Use of Computers in Revision, and How to Establish a Web Site to Display Student Writing.
Keywords: English language,Tiếng Anh; Composition and exercises,Thành phần và bài tập